SIKAP ETIS PENDIDIK KEPADA SISWA DALAM MEMBENTUK GLOBAL CITIZEN BERDASARKAN PANCASILA - Yashoki Gea (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Ethical attitude is the attitude of an educator showing, teaching, and theorizing in accordance with the norms and values of Pancasila. An educator is able to theorize correctly and also be able to run the theory in his life (teaching theory) and (doing theory). Both of these must be in harmony with the profession as an educator to form learners who have high tolerance values in the midst of the plural. Students is a generation of nations that build, improve and promote the nation. So an educator should teach the values of Pancasila so that the nation's generation has an attitude of nationalism by appreciating every difference (religion, race, language, culture) in Indonesia. With the formation of an attitude through education, then pluralism at the national level of course also every action undertaken in it will affect the action in shaping the world peace (global citizenship) in the middle of the world. This distinction must always be addressed properly in order to avoid conflicts and disunity. One of the steps that must be taken to apply the values of Pancasila as the basic ideology of the state by not forgetting the basic state of the 1945 Constitution Keywords— Ethical Attitudes, Pancasila, Educators, Global Citizens, Students.